Beyond the march of death : memoir of a soldier's journey from Bataan to Nagasaki - McBride, Myrrl W. (McFarland & Co., 2010)
"The story begins with the news of Pearl Harbor just reaching the Philippine Islands, continuing through the courageous stand of the 200th Coast Guard Artillery in the Battle of Bataan, the Death March, and Myrrl W. McBride, Sr.'s, three and half years as a prisoner of war in Japanese camps"--Provided by publisher.